The complete chloroplast genome of Chinese medicinal herb Belamcanda chinensis (L.) Redouté (Iridaceae). Issue 2 (1st February 2021) - Li, Cuicui; Hu, Saiwen; Ding, Yining; Bi, Guangyao; Su, Chun; Xia, Zhi
Abstract: The species of Belamcanda chinensis (L.) Redouté. is one of the Chinese traditional medicinal herb. In this study, we first report the complete chloroplast (cp) genome of B. chinensis . The chloroplast (cp) genome was determined to be 153, 735 bp and the GC contents was 37.9%. The sequence includes a large single-copy (LSC) region of 83, 199 bp, a small single-copy (SSC) region of 18, 168 bp, and two separated inverted regions of 26, 184 bp each. It contains 132 genes, including 86 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. Based on 10 chloroplast genomes data, the maximum likelihood phylogenetic analysis revealed that B. chinensis was sister to Iris (Bootstrap = 100%) within Iridaceae. This result will be helpful for the conservation and breeding programs of the B. chinensis.